ANALISIS YURIDIS TERHADAP PUTUSAN PERKARA TINDAK PIDANA PERKOSAAN NOMOR:205/Pid.B/2022/PN.BKN - Lubis, Karlina; Heriyanti, Yuli; Saputra, Rian Prayudi (Pahlawan Tuanku Tambusai University, 2024)
The crime of rape is regulated in Article 285 of the Criminal Code, Chapter XIV concerning crimes against decency. The purpose of this research is to analyze the juridical judgment of the judge's decision and determine the basis of the Public Prosecutor in making criminal charges against the perpetrator of the crime of rape in case Number: 205/ Pid.B/ 2022/PN.Bkn. The type of research used in this research is normative juridical, while the nature of this research uses descriptive qualitative. The first research result in this research is that the sentence of imprisonment for 7 (seven) years in prison imposed by the Panel of Judges in Decision Number 205/Pid.B/2022/PN.BKN is correct, considering that this case is still an attempted rape taking into account Article 285 Criminal Code (KUHP) Juncto. Article 53 paragraph (1) of the Criminal Code (KUHP), the criminal decision handed down by the Panel of Judges can be reduced by one third, which means a maximum penalty of 7 (seven) years in prison, the second being the basis for the Public Prosecutor's demands regarding the charges. given with special subjective consideration, namely the public prosecutor's thoughts, feelings and assessment of the defendant, however, regarding the imposition of the punishment demanded by the public prosecutor against the defendant, it does not fulfill the sense of justice for the victim because the public prosecutor gave his demand for the defendant to be imprisoned for 5 (five) years in prison. Keyword: Juridical Analysis, Crime, Rape